The changing pattern of acute spinal referrals during primary and secondary waves of the COVID‐19 pandemic. (13th September 2021) - Naskar, Rajib; Baryeh, Kwaku W.; Pavuluri, Sindhu; Rajagopal, Trichy
Abstract: Introduction: The COVID‐19 pandemic has had a devastating effect on health systems globally. This led to changes in patient access to healthcare particularly spinal services. This study investigates the impact of the pandemic on the volume of patients being referred to and accessing spinal services during both the first and second waves. Methods: All emergency spinal referrals and related hospital attendances to the emergency department in a busy district general hospital were analysed. The data were evaluated at three time points each covering a 3‐month period. Data collected included patient demographics, duration and nature of symptoms, reason for referral, clinical and MRI findings, length of stay in hospital, any interventions performed and the follow‐up plan. Results: There were a total of 316 emergency referrals across the three time periods. The number of referrals fell by 15% between the pre‐COVID‐19 period and the first wave. Comparing the first and second waves, the number of referrals was increased by 58%. Comparing the second wave to the pre‐COVID‐19 period, referrals were 34% greater in the second wave ( p  < 0.005). Conclusion: We highlight an increase in referrals to our spinal service during the secondary wave, having fallen during the first wave. We hypothesise that the increase in referrals, despite similar restrictions to the first wave, is a result of changing patterns of behaviour due to the fear of contracting COVID during the first wave and difficulty in accessing primary care services in the second wave.